Influence of storage conditions on MALDI-TOF MS profiling of gingival crevicular fluid: Implications on the role of S100A8 and S100A9 for clinical and proteomic based diagnostic investigations - Preianò, Mariaimmacolata; Maggisano, Giuseppina; Lombardo, Nicola; Montalcini, Tiziana; Paduano, Sergio; Pelaia, Girolamo; Savino, Rocco; Terracciano, Rosa (Proteomics (Weinheim), 2016)
Gingival crevicular fluid (GCF) may be a source of diagnostic biomarkers of periodontitis/gingivitis. However, peptide fingerprints may change, depending on GCF collection, handling and storage. We evaluated how storage conditions affect the quality and the reproducibility of MALDI‐TOF profiles of this fluid. GCF was collected on paper strips from four subjects with healthy gingiva. Our findings demonstrated that sample storage conditions significantly affect GCF peptide pattern over time. Specifically, the storage of GCF immediately extracted from paper strips generates less variations in molecular profiles compared to the extraction performed after the storage. Significant spectral changes were detected for GCF samples stored at –20°C directly on the paper strips and extracted after three months, in comparison to the freshly extracted control. Noteworthy, a significant decrease in the peak area of HNP‐3, S100A8, full‐length S100A9 and its truncated form were detected after 3 months at –80°C. The alterations found in the “stored GCF” profile not only may affect the pattern‐based biomarker discovery but also make its use not adequate for in vitro diagnostic test targeting S100A8, S100A9 proposed as potential diagnostic biomarkers for periodontal disease. In summary, this study shows that the best preserved signatures were obtained for the GCF samples eluted in trifluoroacetic acid and then immediately stored at –80°C for 1 month. The wealth of information gained from our data on protein/patterns stability after storage might be helpful in defining new protocols which enable optimal preservation of GCF specimen.